Apakah Kelelahan Kerja Berhubungan dengan Produktivitas Kerja? - Villia Pingkan Nayoan; Lery Fransil Suoth; Jeini Ester Nelwan (Universitas Sam Ratulangi, 2020)
Work productivity is a mental attitude based on the principle. Work productivity was influnced by several factors such as age, temperament, individual physical condition, fatigue, work motivation, physical conditions such as sound, lighting, rest time, work duration, wages, organizational form, social environment, and family. The purpose of this research was to analyzed the correlattion between work fatigue with work productivity in Likupang highway construction project workers at PT. Monalisa Jaya. This research was conducted on Likupang Highway Construction Project Workers At PT. Monalisa Jaya in September-October 2019. This research was an quantitative research using a cross-sectional study design. The population in this research was all field workers at PT Monalisa Jaya, amount to 37 workers. The sample in this research was conducted in total population. Based on the results of research conducted on-field workers at PT. Monalisa Jaya found that PT.Monalisa Jaya shows that most moderate and high work fatigue. In other side, the work productivity was categorized on high. There was a correlattion between work fatigue and work productivity (p=0,001). The conclusion of this research showed that work fatigue has correlattion to work productivity.